GSK3β Interacts With CRMP2 and Notch1 and Controls T-Cell Motility - Fazil, Mobashar Hussain Urf Turabe; Prasannan, Praseetha; Wong, Brandon Han Siang; Kottaiswamy, Amuthavalli; Salim, Nur Syazwani Binte Mohamed; Sze, Siu Kwan; Verma, Navin Kumar (Frontiers in Immunology, 2021)
The trafficking of T-cells through peripheral tissues and into afferent lymphatic vessels is essential for immune surveillance and an adaptive immune response. Glycogen synthase kinase 3β (GSK3β) is a serine/threonine kinase and regulates numerous cell/tissue-specific functions, including cell survival, metabolism, and differentiation. Here, we report a crucial involvement of GSK3β in T-cell motility. Inhibition of GSK3β by CHIR-99021 or siRNA-mediated knockdown augmented the migratory behavior of human T-lymphocytes stimulated via an engagement of the T-cell integrin LFA-1 with its ligand ICAM-1. Proteomics and protein network analysis revealed ongoing interactions among GSK3β, the surface receptor Notch1 and the cytoskeletal regulator CRMP2. LFA-1 stimulation in T-cells reduced Notch1-dependent GSK3β activity by inducing phosphorylation at Ser9 and its nuclear translocation accompanied by the cleaved Notch1 intracellular domain and decreased GSK3β-CRMP2 association. LFA-1-induced or pharmacologic inhibition of GSK3β in T-cells diminished CRMP2 phosphorylation at Thr514. Although substantial amounts of CRMP2 were localized to the microtubule-organizing center in resting T-cells, this colocalization of CRMP2 was lost following LFA-1 stimulation. Moreover, the migratory advantage conferred by GSK3β inhibition in T-cells by CHIR-99021 was lost when CRMP2 expression was knocked-down by siRNA-induced gene silencing. We therefore conclude that GSK3β controls T-cell motility through interactions with CRMP2 and Notch1, which has important implications in adaptive immunity, T-cell mediated diseased and LFA-1-targeted therapies.